USING STATISTICAL TOOLS TO DETECT GASOLINE ADULTERATION - Barbeira, Paulo Jorge Sanches (Revista de Engenharia Térmica, 2002)
Histograms and normal distribution curves (Gaussian fit) were used to determine the average composition of the gasoline commercialized in the state of Minas Gerais, Brazil, and to detect samples with atypical composition. Atypical composition may rise from the fact that the gasoline comes from distinct sources (refinery or petrochemical plant) or may be due to the careful addition of industrial solvents. A considerable number of samples of atypical composition have been detected despite the samples tested having the same source. This statistical analytical tool has been shown useful in the evaluation of fuel quality.